The Public Safety (Public Protection Orders) Bill 2012: Is Post-Sentence Detention of Sex Offenders Consistent with Human Rights? - Moran, Jasmin (Victoria University of Wellington Law Review, 2014)
This article examines the human rights consistency of the Public Safety (Public Protection Orders) Bill 2012. The Bill proposes a new scheme to detain recidivist sex offenders beyond the expiration of their finite sentences, if they are seen as highly likely to reoffend. Despite obvious human rights concerns, the Attorney-General issued a statement contending the Bill was consistent with the New Zealand Bill of Rights Act 1990. The article analyses the correctness of that statement, with a particular focus on whether the Bill establishes a form of civil committal and is, in substance, different to prison detention.